COVID-19 through Bolsonaro's speech: old sources for a new disease - Siqueira, Maity; Tota, Felippe; Ferrari, Caroline Girardi; Duarte, Sergio; Lipert, Luiz Felipe; Garcia, Fernanda (Revista virtual de estudos da linguagem, 2025)
In the context of Brazil's alarming COVID-19 death toll, metaphors in the discourse of former President Jair Bolsonaro seemed to minimize the magnitude of the pandemic scenario. Our goal is to analyse his use of figurative language in response to the widespread transmission of the virus in Brazil. We departed from the hypothesis that war, religion, and health mappings would be plentiful in Bolsonaro's speeches, considering his military past, religious beliefs, and the current pandemic. Our corpus consists of excerpts from Bolsonaro's public speeches, ranging from March 10th, the day the subject started to be addressed on the government website, to mid-August 2020, when Brazil surpassed 100,000 deaths. Bolsonaro's metaphorical utterances regarding COVID-19 were identified using the Metaphor Identification Procedure (Pragglejaz Group, 2007). In our results, WAR, a common source domain in politics, was one of the most used ones by Bolsonaro to talk about COVID-19 and its consequences. Linguistic instantiations of health and religious source domains were not frequent. Instead, religious beliefs came up as a frame that often underlies his speech. Moreover, results point to the possibility that Bolsonaro's speeches instantiate the Strict Father Model (Lakoff, 1996; 2004), a framework that describes conservative politics in the US.